Соціальні гарантії працівникам промисловості за умовами праці - Новікова, О.Ф.; Логачова, Л.М. (Економіка промисловості, 2018)
У статті розглянуто діючу систему пільг і компенсацій працівникам, зайнятим у шкідливих і небезпечних умовах праці на підприємствах промисловості. Визначено основні проблеми управління професійними ризиками, виявлено недоліки діючої системи пільг і компенсацій. Відзначено відсутність надійних критеріїв і методів оцінки впливу умов праці на здоров'я працівників і тривалість періоду трудової діяльності.Проаналізовано показники, що характеризують стан умов праці у промисловості, виявлено тенденцію до зменшення чисельності зайнятих у шкідливих і небезпечних умовах праці при одночасному зростанні питомої ваги цієї категорії в обліковій кількості штатних працівників. На підприємствах промисловості відзначено зростання питомої ваги зайнятих в умовах перевищення гігієнічних нормативів за такими факторами, як мікроклімат, виробничий шум, ультразвук, інфразвук, хімічні фактори, важкість і напруженість праці.Виявлено стійку тенденцію перевищення кількості працюючих, яким встановлені пільги і компенсації за умовами праці, над кількістю зайнятих у шкідливих і небезпечних умовах.Встановлено, що найбільш вагомою пільгою є право на дострокову пенсію. Проаналізовано обсяги фінансових ресурсів Пенсійного фонду України, що надійшли від підприємств на виплату дострокових пенсій, а також витрати на ці цілі коштів Державного бюджету України.Обґрунтовано необхідність формування професійних пенсійних фондів з метою збереження соціальних гарантій охорони праці працівникам промисловості, зайнятим у несприятливих умовах праці. В статье рассмотрена действующая система льгот и компенсаций работникам, занятым во вредных и опасных условиях труда на предприятиях промышленности. Определены основные проблемы управления профессиональными рисками, выявлены недостатки действующей системы льгот и компенсаций. Отмечено отсутствие надежных критериев и методов оценки влияния условий труда на здоровье работников и продолжительность периода трудовой деятельности.Проанализированы показатели, характеризующие состояние условий труда в промышленности, выявлена тенденция к уменьшению численности занятых во вредных и опасных условиях труда при одновременном росте удельного веса этой категории в учетной численности штатных работников. На предприятиях промышленности отмечен рост удельного веса занятых в условиях превышения гигиенических нормативов по таким факторам, как микроклимат, производственный шум, ультразвук, инфразвук, химические факторы, тяжесть и напряженность труда.Выявлена устойчивая тенденция превышения количества работающих, которым установлены льготы и компенсации по условиям труда, над количеством занятых во вредных и опасных условиях.Установлено, что наиболее весомой льготой является право на досрочную пенсию. Проанализированы объемы финансовых ресурсов Пенсионного фонда Украины, поступившие от предприятий на выплату досрочных пенсий, а также расходы на эти цели средств Государственного бюджета Украины.Обоснована необходимость формирования профессиональных пенсионных фондов с целью сохранения социальных гарантий охраны труда работникам промышленности, занятым в неблагоприятных условиях труда. The paper considers the current system of benefits and compensation to persons, engaged in harmful and dangerous labour conditions at industrial enterprises. The main problems of professional risks management are identified. The shortcomings of the current Ukrainian system of benefits and compensation for persons, employed in industry, are revealed. It has beenunderlined, that in Ukraine there is a lack of reliable criteria and methods for assessing the impact of labour conditions on the health of persons, employed in industry, and the length of the period of work.The indicators, describing the state of labour conditions in Ukrainian industry are analyzed. The tendency to decrease the number of employees in harmful and dangerous labour conditions is revealed, while the share of this category of workers in the total number of regular employees is growing at the same time. Also at industrial enterprises the growth in the proportion of employees, who work in conditions of exceeding hygienic standards for such factors as microclimate, production noise, ultrasound, infrasound, chemical factors, severity and labour intensity, was noted.It has been revealed, that in Ukraine there is a stable tendency of exceeding the number of employees, who becomes beneficiaries and receives compensations for labour conditions, over the number of persons, employed in harmful and dangerous labour conditions.It is established, that the most significant benefit for persons, employed in industry, is the right to early retirement. The volume of financial resources of the Pension Fund of Ukraine, received from enterprises for the payment of early retirement pensions, as well as the outflows of the State Budget funds of Ukraine for this objective are analyzed.The necessity of professional pension funds’ formation with the purpose of preserving social guarantees of labour protection for persons, employed in industry and engaged in unfavourable labour conditions, is proved.